Software and Online Publications (Journal of Science-Innovative Research in Uzbekistan, 2025)
The field of software and online publications has evolved significantly with the rise of digital media, where technology now plays an indispensable role in the creation, management, and distribution of content. This transformation is driven by the development of specialized software tools designed to streamline the publishing process, enabling a broader range of individuals—from professional publishers to independent content creators—to engage in digital publishing.